PENGARUH LDR, SUKU BUNGA, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2014-2023 - Iftitah Hisanah Shabri; Nur Laila Robiati; Tiara Nabila Nur Wibawanti (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
This study was conducted to identify the influence of LDR, interest rates, and inflation on economic growth in Indonesia. This study applies a quantitative method that utilizes secondary data through multiple linear regression analysis based on annual time series data obtained from SEKI BI and BPS, and in the period 2014 to 2023. The results of the regression data analysis indicate that individually, LDR, interest rates, and inflation do not have a significant impact on economic growth in Indonesia. Likewise, simultaneously, the three independent variables do not show a significant influence on economic growth with a Prob (F-statistic) value of 0.5325 > 0.05. The coefficient of determination (R²), which is 0.2886, shows that only 28.86% of the variation in economic growth can be explained by these three variables, the rest is influenced by other factors outside this study model. The results of this study indicate that LDR, interest rates, and inflation are weak as monetary policy transmission mechanisms during this period. This study is expected to serve as a guideline for policymakers, academics, and practitioners to understand the dynamics of Indonesia's economic growth, as well as provide opportunities for more in-depth research with more diverse variables and more detailed data.